PENGARUH MOTIVASI, LINGKUNGAN KERJA FISIK, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA SATUAN KERJA PUSAT REHABILITASI KEMENTERIAN PERTAHANAN REPUBLIK INDONESIA - Wibowo, Diah Ayu Retnowati; Faeni, Dewi Puspaningtyas (SINERGI : Jurnal Riset Ilmiah, 2025)
This study examines the impact of work motivation, physical work environment, and job satisfaction on employee performance within the Rehabilitation Center Work Unit of the Ministry of Defense of the Republic of Indonesia (Satker Pusrehap Kemhan RI). Adopting a quantitative research design with descriptive and causal-associative approaches, data were collected from 49 employees selected through random sampling. A structured questionnaire was utilized as the primary data collection instrument. Multiple linear regression analysis, complemented by t-tests and F-tests, was employed to evaluate the hypotheses. The results demonstrate that work motivation (t = 2.504), physical work environment (t = 3.514), and job satisfaction (t = 2.786) each have a positive and statistically significant effect on employee performance, exceeding the critical t-value (2.012). Furthermore, the joint influence of work motivation and job satisfaction is significant (F = 2.506 > 1.83; p = 0.006). These findings underscore the strategic importance of fostering employee motivation, ensuring optimal physical workplace conditions, and enhancing job satisfaction to improve overall performance. The study recommends that human resource management policies integrate these factors as core priorities             to strengthen organizational efficiency and effectiveness.